IMPLEMENTATION OF INFORMATION SYSTEM AUDIT TO IMPROVE INTERNAL CONTROL ON ACCURATE 5 AND ZAHIR 6 - Wahyudi, Felincia; Antonio, Gregorius Rudy (jfpublisher, 2024)
Large funds are used by organizations to invest in business applications to achieve the strategic and business operational goals of the organization. Running business operations using applications which are closely related to technology comes with the risk of bugs, errors, and similar issues. This risk will lead to a negative impact on the output of information that may cause errors and data loss. To prevent this from happening, the proper action that needs to be applied to overcome the risk is by conducting an information system audit on the application control that is implemented. An information system audit is an audit process carried out to determine whether the application or information system implements a sufficient control system. Application control testing is an important thing to do to overcome potential risks that could threaten the application. This research applied qualitative descriptive approach. This research aims to identify whether Accurate 5 and Zahir 6, the two accounting software applications, have been designed appropriately and could be operated effectively. The research findings indicate that the Accurate and Zahir applications implement controls, however, there are some weaknesses that should be fixed to improve internal control. In the Accurate application, there were differences in output results for reports, date entries that exceeded the limit, and sign checks on unit prices. Whereas in the Zahir application, it was identified that there were discounts entered that exceeded the range and sales reports that were not varied.